(untitled) (Clinics, 2012)
OBJECTIVE: The aim of this study was to evaluate the treatment of patients with chronic lesions in the posterolateral corner of the knee with reconstruction of the fibular collateral ligament, popliteus tendon and popliteofibular ligament and with autografts of the biceps femoris and fascia lata. METHOD: A total of 129 patients with injuries of the posterolateral corner of the knee that lasted for more than three weeks and were associated with the lesion of at least one of the cruciate ligaments were included. All of the patients were operated on consecutively in the same hospital between March 2004 and April 2009. Clinical evaluation using the Lyshom scale and the International Knee Documentation Committee (IKDC, item 4, assessment ligament) protocol was performed in 114 patients for whom there were complete data available. RESULTS: There was significant improvement in the Lyshom score and improved stability according to the IKDC protocol in the pre- compared to postoperative varus stress test at 30 degrees and the posterolateral rotation test. CONCLUSIONS: Surgical reconstruction of the posterolateral corner of the knee with biceps femoris tendon and fascia lata autografts is effective in stabilizing the posterolateral corner of the knee.